(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article, special attention is paid to the study of objects of applied art of the peoples of Uzbekistan, in particular, these are traditional textiles, accessories, clothing and interior items. The study is intended to reveal the artistic potential inherent in the national cultural tradition and determine the best ways to borrow it.